Cisplatin or carboplatin in the treatment of non-small cell lung cancer: a comprehensive review - Marcello Tiseo; Andrea Ardizzoni (Oncology Reviews, 2011)
Cisplatin has a pivotal role in the treatment of non-small cell lung cancer (NSCLC). However, it is associated with a number of serious and unpleasant side effects (nausea-vomiting, myelo-suppression, neuro-toxicity and renal function impairment). To overcome these limitations, most clinicians have turned towards the use of the cisplatin analog carboplatin, which is associated with a lower incidence of toxicity. Although carboplatin and cisplatin have a similar mechanism of action and pre-clinical spectrum of activity, it is still unclear whether they actually have the same clinical efficacy in all types of tumors. While for some tumors, such as ovarian cancer, equivalent efficacy has been convincingly proven, for others, such as germ cell and headneck tumors, there is some evidence that carboplatin is inferior to cisplatin. It has never been convincingly proven that carboplatin and cisplatin have the same efficacy in the treatment of NSCLC. This review provides an update of available evidences about this important scientific question.